SOCIAL AND MARKETING ASPECTS OF TRANSFORMATION PROCESSES IN UKRAINE IN CONDITIONS OF EUROPEAN INTEGRATION - M. V. Martynenko; O. K. Gerasimov; O. O. Iastremska (Фінансово-кредитна діяльність: проблеми теорії та практики)
The successful transition of transformation processes in Ukraine under the conditions of European integration is possible only with the intensification of the competitive advantages of the country, the main of which is human intellectual capital. Unfortunately, current data on migration processes show an active outflow of intellectual capital from Ukraine. In such conditions, there is a need to find additional tools for influencing migration processes to reduce the outflow of intellectual capital from Ukraine. One of such tools is social marketing. The significance of social marketing for transformational processes is determined by its focus on promoting new ideas in society, effective influence on selected target groups and changing their behavior in order to get benefits not only for individuals but also for the society, taking into account its needs in the conditions of limited resources. The purpose of the research is to substantiate the areas of improvement of the transformation processes in Ukraine in the conditions of European integration, based on the use of social marketing tools. The article analyzes the theoretical approaches to the definition of the essence of transformation, examines the position of Ukraine in world ratings, reflecting the effectiveness of the transformation processes in different countries. The approaches to the definition of the essence of social marketing and its importance for the transformational processes in society are substantiated. The possible outcomes for society as a result of changes in behavior and the choice of Ukrainian youth in favor of study and work in Ukraine instead of emigration abroad are considered. The peculiarities of the 4P model in social marketing are presented in order to preserve intellectual capital in Ukraine. The directions of application of social marketing tools for improvement of transformation processes in Ukraine in the conditions of European integration are substantiated.